2016
DOI: 10.1089/jpm.2016.0160
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Ethnic Attitudes Toward Physician-Assisted Death in California and Hawaii

Abstract: Background: As aid-in-dying laws are gaining more public acceptance and support, it is important to understand diverse perceptions toward physician-assisted death (PAD). We compare attitudes of residents from California and Hawaii to identify variables that may predict attitudes toward PAD. Methods: A cross-sectional online survey of 1095 participants (a 75.8% survey completion rate) from California and 819 from Hawaii (a 78.4% survey completion rate). Data were collected between July through October 2015.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(41 reference statements)
1
17
2
Order By: Relevance
“…Periyakoil et al also, found that ethnicity and gender were not significant predictors. [29] In contrast, and as discussed above, the findings from this research revealed ethnicity as a strong predictor of choosing ‘measures to help me die peacefully’. Respondents who self-identified as ‘black’ or non-white were less likely to select this option.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Periyakoil et al also, found that ethnicity and gender were not significant predictors. [29] In contrast, and as discussed above, the findings from this research revealed ethnicity as a strong predictor of choosing ‘measures to help me die peacefully’. Respondents who self-identified as ‘black’ or non-white were less likely to select this option.…”
Section: Discussioncontrasting
confidence: 46%
“…[29] Periyakoil et al found that older respondents were significantly more supportive of PAD, and that those who reported spiritual or religious beliefs were significantly supportive of PAD. Periyakoil et al also, found that ethnicity and gender were not significant predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Research efforts should address new disparity concerns in California, which center on unequal access to PAD in patients who qualify but cannot afford medications, or lack resources or time to comply with safeguards. They should also examine the perception that PAD legalization represents devaluation of life by the health care system, and study normative effects of PAD legalization on attitudes about death and dying over time.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…For example, an online survey conducted in California found that support for access to PAD varied by ethnicity, being highest among non-Hispanic white respondents (75.6%) and lowest among African American respondents (59.6%). 7 Continued open dialogue about these issues is needed. We agree with Dr. Sethi that health care providers need to be prepared to discuss these issues.…”
Section: Letter Re: High Hypothetical Interest In Physician-assisted mentioning
confidence: 99%